Deposition of CdS Thin Film by Thermal Evaporation - Dey M.; Das N.K.; Sen Gupta A.K.; Dey M.; Hossain M.S.; Matin M.A.; Amin N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Borosilicate glass; Cadmium sulfide; Cadmium sulfide solar cells; Cadmium telluride; Carrier concentration; Chemical beam epitaxy; Chemical vapor deposition; Electrochemical deposition; II-VI semiconductors; Light emitting diodes; Molecular beam epitaxy; Optoelectronic devices; Photonic devices; Pulsed laser deposition; Reduction; Screen printing; Sol-gels; Solar cells; Spray pyrolysis; Substrates; Thermal evaporation; Thin film circuits; Thin film solar cells; Vacuum evaporation; Borosilicate glass substrates; CdS thin films; CdS/CdTe solar cells; CdS/CdTe thin film solar cells; Chemical vapour deposition; Chemical-bath deposition; Thermal evaporation technique; VCM 600 Vl; Thin films